PROGNOSTIC VALUE OF SEX-DETERMINING REGION Y-BOX 2 (SOX2) IN PROSTATE CANCER - HADEEL I MOHASEN,; BASIM SHEHAB AHMED, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objectives of this study were to evaluate the expression of sex-determining region-Y BOX 2 (SOX2) markers and their association with clinicopathological parameters. Methods: A cross-sectional study was carried out to involve 90 specimens from patients diagnosed with prostatic cancer (PC) and benign prostatic hypertrophy (BPH) compared with positive control (human bronchial tissue for SOX2 marker) with each run. Results: The highest proportion of specimens of PC was graded ≤7 by Gleason grading system (53.3%). There were significant associations (p<0.05) between all this cancer stem cell marker results and prevalence of PC. Positive SOX2 marker result was significantly associated with bad prognostic sign (81.3%, p=0.001). This marker was highly sensitive (100%) specificity (82.4%), with high accuracy (90%). Conclusion: There was a significant expression of SOX2 in prostate adenocarcinomas. SOX2 can be considered as a key regulator of tumor progression, aggressive behavior, and metastasis. Furthermore, it is a reliable marker for the early diagnosis and the designed chemotherapy of prostate adenocarcinomas.